When Meaning Collapses: Nihilism, Violent Extremism, and the Promise of Logotherapy - Zora Arfina Sukabdi (Journal Psikologi Forensik Indonesia, 2026)
Contemporary violent extremism among youth is increasingly defined by existential vulnerability as well as ideological commitment. Recent cases in Indonesia involving adolescents exposed to extremist content via digital platforms indicate a shift away from traditional forms of terrorism based on organized recruitment, religious indoctrination, and political grievances and toward more fragmented forms of radicalization shaped by "salad bar ideologies," identity confusion, and meaninglessness. These developments underline the need of examining violent extremism through the prism of nihilism and the human search for meaning. This article will look at how Friedrich Nietzsche's concept of nihilism and Viktor Frankl's logotherapy might help us comprehend modern radicalization and propose preventive treatments. The study employs a literature review approach, analyzing important works by Nietzsche and Frankl as well as contemporary scholarship on nihilism, meaning in life, radicalization, and violent extremism. The review defines nihilism as an existential vacuum defined by the loss of meaning, purpose, and significance. Nietzsche's diagnosis of nihilism is still relevant for understanding the psychological and cultural factors that may heighten sensitivity to extremist narratives. However, his emphasis on self-created meaning arose from the historical context of European modernity and may be less applicable in communities whose meaning is drawn primarily from family, church, community, and social responsibility. In contrast, Frankl's logotherapy views meaning as something that can be discovered via relationships, responsibility, contribution, and attitudes toward suffering, making it more flexible to a variety of cultural situations. The findings indicate that meaning-centered methods could supplement traditional counter-radicalization strategies. Logotherapy-based interventions can assist at-risk individuals manage existential vulnerabilities by improving their sense of purpose, belonging, responsibility, and prosocial identity. Such approaches present a viable foundation for prevention, rehabilitation, and reintegration efforts in Indonesia and other non-Western settings.